Electromechanical coupling modelling of distributed MEMS phase shifter for phased array antennas. Issue 8 (3rd August 2018) - Wang, Congsi; Ying, Kang; Li, Haihua; Gao, Wei; Yin, Lei; Wang, Meng; Peng, Xuelin; Wang, Shaoxi
ABSTRACT: MEMS phase shifter has many advantages as the 'steering wheel' of phased array antenna beam steering. The deformation of mechanical structures of MEMS phase shifter influenced by the complex environmental factors, which became the biggest obstacle to further enhance the performance of phased array antennas. The electromechanical coupling model between the bridge height and phase shift of the distributed MEMS phase shifter is developed. The coupling model could be used to predict the phase error and determine the bridge height tolerance for the deformed MEMS phase shifter. The simulation results of four-bit distributed MEMS phase shifter with 15 bridges illustrate the validity of coupling model and demonstrate the application potential for engineering design and test.